Materials 2017
DOI: 10.18690/978-961-286-056-1.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Building Materials for Low-Rise Buildings Based on Environmental Footprint

Abstract: The aim of SEEP2017 is to bring together the researches within the field of sustainable energy and environmental protection from all over the world.The contributed papers are grouped in 18 sessions in order to provide access to readers out of 300 contributions prepared by authors from 52 countries.We thank the distinguished plenary and keynote speakers and chairs who have kindly consented to participate at this conference. We are also grateful to all the authors for their papers and to all committee members.We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…The midpoint environmental impact indicators of the cool paint from this study were compared with the results reported in the literature that investigated the midpoint environmental impact of insulation materials. The average values of the study of [38] were reported in Table 7 because different U-values of insulation construction were assessed. From the comparison presented in Tables 7 and 8, it can be seen that the CTGA/CTSI/CTGR environmental impacts of the cool paint are lower than insulation materials.…”
Section: Comparison With Lca Studies Of Insulation Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The midpoint environmental impact indicators of the cool paint from this study were compared with the results reported in the literature that investigated the midpoint environmental impact of insulation materials. The average values of the study of [38] were reported in Table 7 because different U-values of insulation construction were assessed. From the comparison presented in Tables 7 and 8, it can be seen that the CTGA/CTSI/CTGR environmental impacts of the cool paint are lower than insulation materials.…”
Section: Comparison With Lca Studies Of Insulation Materialsmentioning
confidence: 99%
“…presents the CTGA GWP and TAP of the cool paint compared with the CTGA of the RockWool (RW), Expanded Polystyrene (EPS) and Wood Fibre (WF) for wall and/or roof of low-rise buildings in Central Europe[38]. It also compares CTGA GWP, ODP, POFP, TEP, FEP, MEP and WDP of the cool paint compared with the CTGA of EPS, Mineral Wool (MW) and Phenolic Foam (PF)[39].…”
mentioning
confidence: 99%
See 1 more Smart Citation